1980
DOI: 10.2307/3280582
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruzi-Induced Suppression of the Primary Immune Response in Murine Cell Cultures to T-Cell-Dependent and -Independent Antigens

Abstract: In vitro antisheep erythrocyte (SRBC) and antitrinitrophenyl (TNP) antibody responses of spleen cells obtained from C57BL/6 mice infected with Trypanosoma cruzi were reduced as early as 6 days postinfection and not detectable after 18 days of infection. Lymph node cells had normal antibody responses to SRBC and TNP in vitro until the 11th day of infection, after which responses were diminished. By day 31 of infection, lymph node cells were unresponsive to both SRBC and TNP in vitro. Not only were the antibody … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
1

Year Published

1980
1980
2000
2000

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 21 publications
1
40
0
1
Order By: Relevance
“…Protozoan and metazoan parasites have the ability to depress the immune response of their host to heterologous antigens (49,63,179). Giardia trophozoites have been associated with immunodepression in response to heterologous antigens.…”
Section: Immunosuppression In Infected Micementioning
confidence: 99%
“…Protozoan and metazoan parasites have the ability to depress the immune response of their host to heterologous antigens (49,63,179). Giardia trophozoites have been associated with immunodepression in response to heterologous antigens.…”
Section: Immunosuppression In Infected Micementioning
confidence: 99%
“…Our results indicate that the suppressor activity was localized in plastic-adherent fraction of spleen cell populations isolated from both susceptible A/J and resistant BI0.A mice. Plasticadherent macrophage-like suppressor cells were shown to be the mediators of immunodepression in other flagellate infections such as T. cruzi (Cunningham & Kuhn 1980) and T. rhodesiense (Wellhousen & Mansfield 1979). It is interesting to note that cell subpopulation which is responsible for mediating immunodepression in infections of mice with G. muris, an extracellular protozoan, has similar properties to the cell population which mediates immunodepression for intracellular organisms.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, it is often quite impossible to study the mechanisms leading to immunodepression in parasitic infections without designing in uitro experiments to study the phenomenon. For example, the results M.Belosevic, G.M.Faubert & J.D.MacLean from in vitro studies have shown that macrophage-like suppressor cells play an important role in infections of mice with Trypanosoma cruzi (Cunningham & Kuhn 1980), Trypanosoma rhodesiense (Wellhousen & Mansfield 1979) and Toxoplasma (Suzuki & Kobayashi 1984). Recently, Suzuki & Kobayashi (1984) have identified suppressor macrophage subpopulation in mice infected with Toxoplasma which inhibits the proliferation of lymphocytes by direct contact with the responder target cells.…”
Section: Introductionmentioning
confidence: 99%
“…Infection with the protozoan parasite Trjpanosoma cruzi, as with many parasites, results in the establishment of an immunosuppressed state in the vertebrate host (Rowland & Kuhn 1978b, Cunningham & Kuhn 1980b, Reed, Larsen & Speer 1977, Krettli & Pereira 198 1, Camus et at. 1979.…”
Section: Introductionmentioning
confidence: 99%